Health Related Quality of Life in Patients with Biliary Atresia Surviving with their Native Liver - Sundaram, Shikha S. (2013)
OBJECTIVES: To quantify health related quality of life (HRQOL) of patients with biliary atresia with their native livers and compare them with healthy children and patients with biliary atresia post-liver transplant (LT) and to examine the relationship between HRQOL and medical variables. STUDY DESIGN: A cross-sectional HRQOL study of patients with biliary atresia with their native livers (ages 2-25 years) was conducted and compared with healthy and post-LT biliary atresia samples using PedsQL™ 4.0 child self and parent proxy reports, a validated measure of physical/psychosocial functioning. RESULTS: 221 patients with biliary atresia with native livers (54% female, 67% white) were studied. patient self and parent proxy reports showed significantly poorer HRQOL than healthy children across all domains (p < 0.001), particularly in emotional and psychosocial functioning. Child self and parent proxy HRQOL scores from patients with biliary atresia with their native livers and post-LT biliary atresia were similar across all domains (p=NS). Child self and parent proxy reports showed moderate agreement across all scales, except social functioning (poor to fair agreement). On multivariate regression analysis, black race and elevated total bilirubin were associated with lower Total and Psychosocial HRQOL summary scores. CONCLUSIONS: HRQOL in patients with biliary atresia with their native livers is significantly poorer than healthy and similar to post-LT biliary atresia children. These findings identify significant opportunities to optimize the overall health of patients with biliary atresia.